Critical Thinking Skills and Emotional-Response Discourse: Merging the Affective and Cognitive in Student-Authored Texts through Taxonomy Usage - Ed Comber (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
This essay discusses a taxonomy designed to help students identify emotive-response discourse in their evolving texts, a process that joins emotion and cognitive to foster critical thinking.